Practice of Implementing Self-Evaluation and Madrasah Budget Work Plan - Tawati, Devia Dwi; Muktiyasih, Isma Dwi (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
This study aims to determine the implementation practices of Madrasah Self-Evaluation (EDM) and Madrasah Work Budget Plan (RKAM) at MTs N 6 Boyolali, Central Java. Qualitative research approach with case study design. Data collection techniques through semi-structured interviews and documentation. The subjects of the study included the madrasah quality assurance team consisting of the head of the madrasah, vice head of the madrasah, teachers, representatives of the madrasah committee, parents, and students. Data analysis using Data analysis techniques used by researchers include data collection, reduction, presentation, and drawing conclusions. The results of the study indicate that the implementation of EDM and RKAM is carried out in two stages, namely planning and implementation. EDM planning involves a meeting between the head of the madrasah and the Quality Assurance Team (TPM) to discuss five aspects of EDM, while RKAM planning is carried out by recording stakeholder needs for one year. The implementation of EDM includes the implementation of five aspects (discipline, self-development, learning process, facilities and infrastructure, and financing) which are then documented through the EDM e-RKAM version 2 application. Budget allocation is based on 8 BSNP standards with priority on the learning process and facilities and infrastructure.